Comparison of Substitute Herities between Civil Law and Islamic Law in Indonesia - Nurhidayah, Nurhidayah; Mahsyar, Mahsyar (IAIN Parepare, 2020)
This study discusses the comparison of successor heirs between civil law and Islamic law in Indonesia. This study aims at the system of substitute heirs in the Civil Code and substitute heirs in the Compilation of Islamic Law, as well as a legal comparison of the substitute heirs in the Civil Code and substitute heirs in the Compilation of Islamic Law. This research uses library research or research based on literature. The research method used is literature review, which is a study carried out to solve a problem which basically relies on a critical study of relevant library materials.. Sources of data used in this study are primary data sources, secondary data sources and tertiary data sources. The results of this study indicate, 1) Position of substitute heir in civil law (BW) This is called plaatsvervulling. The replacement of place in inheritance law is called the replacement of heirs, namely the death of a person by leaving grandchildren whose parents have died first; 2) The position of the substitute heir in the perspective of Islamic law, If we look at the provisions of Article 185 KHI paragraph 1, it can be said that a grandchild can act as a substitute heir to replace the position of his parents who have died before the heir, and 3) Comparative law regarding successor heirs that maccording to KHI law: That the child who replaces the father's position is a boy and a girl from a male line whose father died first from the heir. the rights obtained by the successor heirs are not necessarily the same as the rights of the person being replaced, and also may not exceed the share of the heirs who are equal to the one being replaced, but may be reduced. Meanwhile, according to the Civil Code law: that the child who replaces his father's position may be from a male lineage or from a female line, according to the inheritance law of the Civil Code (BW) the portion that will be obtained by the heir who replaces his father's position is exactly the same as the part that should be obtained by his father if his father was still alive from the heir.